Social partnership in development personal and professional rural school students - Badashkeev M. V. (Interactive science, 2016)
in this article we consider the possibilities of social partnership of rural school and the agricultural enterprises, farms, job center in development personal and professional self-determination of rural school students, and also organizational and pedagogical actions are presented to realization of social tests.
Keywords: социальное партнерство; сельский школьник; личностно-профессиональное самоопределение; социальные пробы; personal and professional self-determination; social partnership; social tests; rural school student